Technology tetheredness and creative process engagement during COVID-19: A moderated mediation model of spousal support and cognitive fatigue - Zanaira Iqbal; Asim Faheem; Shoaib Aslam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This research investigates the role of employees and their supervisors by testing how tetheredness to technology during COVID-19, affects employees' job-related outcomes. This study is grounded on conservation of resources theory. It postulates that employees are tethered with technology for job-related activities during COVID-19, resulting in poor work-related outcomes due to cognitive fatigue. Further, this research argues that behavioral demonstration of employees' mental fatigue results in less involvement in work-related creative activities, as assessed by supervisors. Drawing on conservation of resource theory and supervisors' rated of employees engagement during COVID-19 are related to creative activities. Spousal support mitigates the influence of tetheredness to technology on cognitive fatigue. Based on conservation of resources theory, this study proposes that employees are tethered with technology for job-related activities during COVID-19, resulting in poor work-related outcomes due to cognitive fatigue. Data were analyzed by performing a survey on technology professionals in Pakistan. Results showed that tetheredness to technology during COVID-19 is negatively related to employees' creative process engagement. Furthermore, cognitive fatigue more negatively influenced the focal relation. Moreover, for employees with higher spousal support, tetheredness to technology during COVID-19 may not be complicated and might even help-finings spousal support; however, this influence depends upon employee interpersonal factors as well. The findings of this research may help organizations to understand the impact of organizational expectations regarding connectivity during work from home.
Keywords: 330; conservation of resource theory; tetheredness to technology; COVID-19; cognitive fatigue; supervisor-rated employee creative process engagement; spousalsupport